2006
DOI: 10.1080/00365510600977737
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mode of delivery on maternal–neonatal plasma antioxidant status and on protein S100B serum concentrations

Abstract: The increased S100B serum levels in the mothers of group B, post-delivery, may have been due to the long-lasting, oxidative and/or psychogenic stress. The observed remarkably high levels of S100B in the group B newborns may have been due to compressive conditions on the foetus brain during this mode of delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 35 publications
3
16
0
Order By: Relevance
“…However, it is important to note that they can be elevated in other settings. S100B levels, for example, are markedly increased by intrauterine growth restriction or chronic hypoxia,30 are is common during recovery from HI),31 perinatal infection/inflammation, central and peripheral hypoperfusion (which are is common during recovery from HI),31 perinatal infection/inflammation,32,33 traumatic delivery,34 pre-existing neural injury,35 treatments such as prenatal maternal glucocorticoids and anesthetics,36,37 and preterm gestational age,38 as well as being affected by the sex of the infant 36,37,39. Further, the brain does not appear to be the only source for S100B and NSE, for example, which may be released from a variety of tissues, including the umbilical cord and placenta 40…”
Section: Introductionmentioning
confidence: 99%
“…However, it is important to note that they can be elevated in other settings. S100B levels, for example, are markedly increased by intrauterine growth restriction or chronic hypoxia,30 are is common during recovery from HI),31 perinatal infection/inflammation, central and peripheral hypoperfusion (which are is common during recovery from HI),31 perinatal infection/inflammation,32,33 traumatic delivery,34 pre-existing neural injury,35 treatments such as prenatal maternal glucocorticoids and anesthetics,36,37 and preterm gestational age,38 as well as being affected by the sex of the infant 36,37,39. Further, the brain does not appear to be the only source for S100B and NSE, for example, which may be released from a variety of tissues, including the umbilical cord and placenta 40…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, S100B is a calcium‐binding protein, predominantly expressed by astrocytes in vertebrate brain (Marenholz et al, 2004), although some evidence has suggested its production in other non‐cerebral tissues, such as adipocytes (Steiner et al, 2007). Increased serum S100B levels have been shown after exposure to stress in rats (Scaccianoce et al, 2004; Diehl et al, 2007) and humans (Schulpis et al, 2006). Serum S100B is influenced by diet and by body weight gain (Holtkamp et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the absence of a serious TAS reduction in the blood of the neonates, especially in those of Group B, which also indicates the peroxidation of lipids, may be due to the presence of low levels of lipids, and, especially, due to the very low LDL levels in the CB of the infants, and/or the placenta protective eVect against oxidative stress (Schulpis et al 2006.…”
Section: Discussionmentioning
confidence: 51%
“…Our previous studies (Schulpis et al 2006 showed that normal and/or prolonged labor and deliveries are implicated with low total antioxidant status (TAS) in mothers, post-delivery. In addition, erythrocyte membrane Na + , K + -ATPase activity was found modulated in athletes after endurance exercise in whom the TAS levels were measured to be low in the blood and their plasma catecholamines were remarkably increased.…”
Section: Introductionmentioning
confidence: 99%